2023
DOI: 10.3390/ijms24043269
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-Derived Antioxidants Alleviate Liver and Adipose Tissue Lipid Disorders and Metabolic Inflammation Induced by High Fat Diet in Mice

Abstract: Obesity induces lipodystrophy and metabolic inflammation. Microbe-derived antioxidants (MA) are novel small-molecule nutrients obtained from microbial fermentation, and have anti-oxidation, lipid-lowering and anti-inflammatory effects. Whether MA can regulate obesity-induced lipodystrophy and metabolic inflammation has not yet been investigated. The aim of this study was to investigate the effects of MA on oxidative stress, lipid disorders, and metabolic inflammation in liver and epididymal adipose tissues (EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Quercetin also significantly restored ROS levels, inhibited growth rates, and apoptosis after exposure to DON and 15-acetyl deoxynivalenol and minimized the toxic effects of DON and 15-acetyl deoxynivalenol . Microorganisms and their byproducts are known to reduce toxicity and protect animal gut microbiota by either degrading or regulating them. , MA are novel, small-molecule nutrients obtained from microbial fermentation and have various effects, including antioxidation, lipid-lowering, and anti-inflammation . MA can also attenuate the damage of various harmful substances to animals and cells. Specifically, Luo et al found that MA can attenuate cobalt chloride-induced mitochondrial function, autophagy, and BNIP3-dependent mitophagy pathways in BRL3A cells .…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin also significantly restored ROS levels, inhibited growth rates, and apoptosis after exposure to DON and 15-acetyl deoxynivalenol and minimized the toxic effects of DON and 15-acetyl deoxynivalenol . Microorganisms and their byproducts are known to reduce toxicity and protect animal gut microbiota by either degrading or regulating them. , MA are novel, small-molecule nutrients obtained from microbial fermentation and have various effects, including antioxidation, lipid-lowering, and anti-inflammation . MA can also attenuate the damage of various harmful substances to animals and cells. Specifically, Luo et al found that MA can attenuate cobalt chloride-induced mitochondrial function, autophagy, and BNIP3-dependent mitophagy pathways in BRL3A cells .…”
Section: Introductionmentioning
confidence: 99%
“…The UHPLC-QTOF-MS analysis revealed that MAs contain 426 metabolites, mainly including organic acids and derivatives (15.96%), organic oxygen compounds (10.80%), organoheterocyclic compounds (7.04%), lipids and lipid-like molecules (6.10%), benzenoids (4.46%), and phenylpropanoids and polyketides (4.23%) [15]. In our prior research, it was documented that MAs exhibit a commendable ability to scavenge free radicals [15], enhance hepatic antioxidant capacity in mothers and offspring [16], and regulate metabolic inflammation in mice [17], but whether MAs can mitigate oxidative stress and inflammatory responseinduced disruption of intestinal epithelial tight junction through the Nrf2-ROS-NLRP3 signaling pathway is unclear. In this study, we employed IPEC-1 cells as a cellular model and developed Nrf2 and NLRP3 knockdown IPEC-1 cells to explore the molecular pathways involved in the impact of MAs on oxidative stress, inflammatory response, and disruption of tight junction proteins.…”
Section: Introductionmentioning
confidence: 99%